Psychological symptoms during the COVID-19 pandemic in Nuevo León - Meza Peña, Cecilia (Consorcio de Universidades Mexicanas A.C., 2023)
Psychological symptoms during the COVID-19 confinement period and their relationship with the perceived impact of the event were evaluated in Nuevo Leon, Mexico. The cross-sectional, correlational study was comprised of 1,872 participants (34.7 % men and 65.3 % women). The Symptom Checklist Revised was used to evaluate the degree of emotional distress and the Impact of Event Scale Revised to evaluate post-traumatic stress symptomatology. Post-traumatic stress was found in 56.5 % of the sample. There is a relationship between the global severity of emotional distress and the dimensions of stress, age, and degree of religious practice. In addition, significant sex differences were found in all the subdimensions of emotional distress, the difference being greater in somatization. There were also significant differences by age group, with emotional distress and post-traumatic stress being higher in those under 35. Having a positive COVID-19 diagnosis generated greater somatizations as well as having someone close to the patient who had died from COVID-19-related causes increased all psychological symptomatology and post-traumatic stress. The onset of confinement had an emotional impact on the population, with the most vulnerable groups being women and those under 35.